Stages of development of streptozotocin-induced experimental diabetes mellitus - Boychuk, T. M.; Grytsiuk, M. I.; Gozhenko, A. I. (Journal of Education, Health and Sport, 2017)
The article presents data about the stages of experimental diabetes mellitus under conditions of the streptozotocin administration. It is noted that in the early development of experimental diabetes, changes in the kidneys proceeds in three stages: physiological adaptation; increasing morphological and functional changes and maladaptation; pathophysiological stage. The data related to changes in glomerular filtration rate, acid excretion, individual morphological alterations, etc. are given. The indicated changes in the opinion of the authors indicate an adaptive reaction of the system of regulation of water-salt metabolism and its main effector organ - the kidneys - to hyperosmia, caused by hyperglycemia with the subsequent formation of diabetic nephropathy.